O invariante E(G, W, M): algumas propriedades e aplicações na teoria de decomposição de grupos - Silva, Letícia Sanches [UNESP] (2013)
In [6], Andrade and Fanti defined the invariant E(G,W,M), where G is a group, W is a G-set and M is a Z2G-module, and presented some results using E(G,W, Z2) ( Z2 seen as a trivial Z2G-module) related to splitting of groups and duality. E(G,W,M) is defined using (co)homology of groups for the pair ((G,W),M) following [14]. The purpose of this work is to present the results given in [6] but adding proofs of some results that were referred but not proved there, such as the invariance ofE(G,W,M) for isomorphic pairs and the independence of the set of orbit representatives in W. We also attempt to generalize some results for any Z2G-m'odulo M (not necessarily Z2) and present some other properties of E(G,W,M), specially for the Z2G-module FTG where T is a subgroup of G, exploring, whenever possible, its relationship with splitting of groups. Many of those results are strongly related with some given in [7] for the invariant of pairs of groups E(G, S,M) where S is a family of subgroups of G.